límites del lenguaje poético en las poéticas de Juan Ramón Jiménez y Emilio Prados - Hernández Pérez, Patricio (Huarte de San Juan. Filología y Didáctica de la Lengua, 2011)
The limitations of poetic language do not rely so much on the combinations and expressive possibilities, always limited, but rather on giving an account of realities that go far beyond the limits imposed by the language. This paper gives brief tour of our literary history to outline some of the linguistic constraints which poets have faced in order to give an account of the richness of their inner world. This tour stops at the work of the Spanish mystics, at the symbolism and at other art movements of the twentieth century to conclude, on account of their paradigmatic values, with a brief sketch of the poetics of Juan Ramón Jiménez and Emilio Prados